Cultivation and Transcriptional Analysis of a Canonical Nitrospira Under Stable Growth Conditions - Mundinger, Aniela B.; Lawson, Christopher E.; Jetten, Mike S. M.; Koch, Hanna; Lücker, Sebastian (Frontiers in Microbiology, 2019)
Nitrite-oxidizing bacteria are vital players in the global nitrogen cycle that convert nitrite to nitrate during the second step of nitrification. Within this functional guild, members of the genus Nitrospira are most widespread, phylogenetically diverse and physiologically versatile, and they drive nitrite oxidation in many natural and engineered ecosystems. Despite their ecological and biotechnological importance, our understanding of their energy metabolism is still limited. A major bottleneck for a detailed biochemical characterization of Nitrospira is biomass production, since they are slow-growing and fastidious microorganisms. In this study, we cultivated Nitrospira moscoviensis under nitrite oxidizing conditions in a continuous stirred tank reactor (CSTR) system. This cultivation setup enabled accurate control of physicochemical parameters and avoided fluctuating levels of their energy substrate nitrite, thus ensuring constant growth conditions and furthermore allowing continuous biomass harvesting. Transcriptomic analyses under these conditions supported the predicted core metabolism of N. moscoviensis, including expression of all proteins required for carbon fixation via the reverse tricarboxylic acid cycle, assimilatory nitrite reduction and the complete respiratory chain. Here, simultaneous expression of multiple copies of respiratory complexes I and III suggested functional differentiation. The transcriptome also indicated that the previously assumed membrane-bound nitrite oxidoreductase, the enzyme catalyzing nitrite oxidation, is formed by three soluble subunits. Overall, the transcriptomic data greatly refined our understanding of the metabolism of Nitrospira. Moreover, the application of a CSTR to cultivate Nitrospira is an important foundation for future proteomic and biochemical characterizations, which are crucial for a better understanding of these fascinating microorganisms.